Assessing long‐term fish responses and short‐term solutions to flow regulation in a dryland river basin. Issue 1 (5th March 2014) - Pool, Thomas K.; Olden, Julian D.
Abstract Water resource development and non‐native species have been cited as primary drivers associated with the decline of native fishes in dryland rivers. To explore this topic, long‐term trends in the fish community composition of the Bill Williams River basin were studied over a 30‐year period (Arizona, USA). We sampled 31 sites throughout the basin that were included in fish surveys by Arizona Game and Fish in 1994–97 and the Bureau of Land Management in 1979–80. We found that non‐native species have proliferated throughout the entire basin, with greater densities in the lower elevations. Native species have persisted throughout most of the major river segments, but have experienced significant declines in frequency of occurrence and abundance in areas also containing high abundances of non‐native species. Next, we assessed the short‐term response of the fish assemblage to an experimental flood event from the system's only dam (i.e. Alamo Dam). In response to the flood, we observed a short‐term reduction in the abundance of non‐native species in sites close to the dam, but the fish assemblage returned to its preflood composition within 8 days of the event, with the exception of small‐bodied fish, which sustained lower postflood densities. Our findings demonstrate the importance of natural flow regime on the balance of native and non‐native species at the basin scale within dryland rivers and highlight minimal effects on non‐native fishes in response to short duration flood releases below dams.